Therapeutic Choice in Older Patients with Acute Myeloid Leukemia: A Matter of Fitness - Raffaele Palmieri; Giovangiacinto Paterno; Eleonora De Bellis; Lisa Mercante; Elisa Buzzatti; Fabiana Esposito; Maria Ilaria Del Principe; Luca Maurillo; Francesco Buccisano; Adriano Venditti (2020)
Acute myeloid leukemia (AML), with an incidence increasing with age, is the most common acute leukemia in adults. Concurrent comorbidities, mild to severe organ dysfunctions, and low performance status (PS) are frequently found in older patients at the onset, conditioning treatment choice and crucially influencing the outcome. Although anthracyclines plus cytarabine-based chemotherapy, also called “7 + 3” regimen, remains the standard of care in young adults, its use in patients older than 65 years should be reserved to selected cases because of higher incidence of toxicity. These adverse features of AML in the elderly underline the importance of a careful patient assessment at diagnosis as a critical tool in the decision-making process of treatment choice. In this review, we will describe selected recently approved drugs as well as examine prognostic algorithms that may be helpful to assign treatment in elderly patients properly.